Identification of type materials of the species of Protypotherium Ameghino, 1885 and Patriarchus Ameghino, 1889 (Notoungulata: Interatheriidae) erected by Florentino Ameghino - Fernández, Mercedes; Fernicola, Juan Carlos; Cerdeño, Esperanza; Reguero, Marcelo A. (Zootaxa, 2018)
The first collections of Interatheriinae (Interatheriidae, Notoungulata) were created by the brothers Florentino and Carlos Ameghino, based on fossil specimens collected from diverse outcrops of Argentina and housed at different national institutions. In order to perform a systematic study of the subfamily, it is essential to revise as much specimens as possible, but first of all those that were used to establish the respective species, that is, the type material. Florentino Ameghino never referred to the collection number of the type specimens of the species he erected in any of his publications; this fact added to the occasional absence of illustrations and adequate descriptions, all of which make their identification a complex task. Thus, when studying the species erected by Florentino Ameghino within Protypotherium and Patriarchus, we recognised a lack of correspondence between some specimens that appeared labelled as types in the collections and the original descriptions of these species. In this contribution, we identify the type specimens of the eleven species of Protypotherium and eight of Patriarchus founded by Florentino Ameghino, housed in the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia” (Buenos Aires, Argentina) and the Zoological Museum of the University of Copenhagen (Denmark). Three case studies are presented: a) specimens correctly identified; b) specimens erroneously catalogued as type material; and c) specimens not established as types in Ameghino’s catalogue, but herein recognised as such. Lectotype and paralectotype of P. antiquum are herein designated.